67.2: A Novel Driving Method to Compensate for RC Delay of Ultra‐Large Size and High Resolution Liquid Crystal Displays. Issue 1 (1st July 2013) - Lee, Seung‐Hyuck; Kim, Jong‐Man; Kim, Kwangjoon; Lee, Seung‐Woo
Abstract We propose a novel method to drive ultra‐large size and high resolution LCD TV with a single‐bank data driver scheme without severe image degradation. We could achieve a maximum luminance and uniformity to be 98cd/m2 and 86%, respectively when gray 128 is displayed. This confirms excellent performance because the conventional dual‐bank driver scheme achieves the counterparts to be 90cd/m2 and 93%.